Formação da identidade pessoal, reconhecimento e educação a partir da perspectiva de Axel Honneth - Tomasi, Rubilar (2019)
I present in this thesis an investigation about the Critical Theory of Axel Honneth, seeking to identify possible contributions to the educational processes, which might be extracted from the argumentation that the formation of intact personal identity depends on three relations of reciprocal recognition and prior recognition. In struggle for acknowledgement, Honneth develops the idea that intersubjective recognition makes the formation of individuals with self-confidence, self-respect and self-esteem possible, which is a condition for having a positive self-relation, for the formation of autonomy and for enabling one´s emancipation. On the other hand, the disrespect, the denial of the acknowledgement and the social pathologies are harmful to formation of personal and collective identity and compromise the socialization of the individual. However, with the expansion of interlocution with others philosophical and psychological conceptions, realizes important modifications and increases in his Critical Theory of acknowledgement, mainly in relation to primacy of recognition over the knowledge and to the social pathologies. It´s aimed in this context, to explain how Honneth defines the formation of the personal identity by means of recognition, what the consequences of the denial of acknowledgement are and what kind of implications this conception of formation has for the educational processes. Defending the thesis that, by dealing with concepts as intersubjective recognition and prior recognition, Honneth develops in an explicit way a concept of personal identity formation that could mean a great contribution for the educational processes, mainly for thinking about elements for a philosophy of education or a recognition pedagogy. I conduct a hermeneutic bibliographic research, with clipping of his published works between the years of 1986 to 2007. For our purposes, we judge important the study of Honneth in this period, because it is in it that is treated in a more direct way the concept of personal identity formation by means of recognition.